2011
DOI: 10.1002/ejoc.201101018
|View full text |Cite
|
Sign up to set email alerts
|

Ritter Reaction: Recent Catalytic Developments

Abstract: The Ritter reaction is a method of choice for the production of amides, which are versatile intermediates in organic synthesis and compounds of interest in natural product synthesis. Recent efforts have been directed towards the development of catalytic versions for the development of more eco‐friendly synthetic routes to amides. This review summarizes the recent progress in this area and covers new applications in the field of Ritter‐type and multicomponent reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
71
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(71 citation statements)
references
References 40 publications
0
71
0
Order By: Relevance
“…Nitriles are employed widely as nitrogen nucleophilic reagents under acidic conditions in Ritter reactions,11 which means nitriles may have a better reactivity than N ‐unsubstituted amides in amidation reactions of simple arenes under acid conditions. Furthermore, our and others’ recent work12 also indicated that the use of nitriles as nitrogen nucleophiles instead of amides can make the synthesis of N ‐arylamides more accessible, because many amides are readily prepared from nitriles by hydrolysis.…”
Section: Methodsmentioning
confidence: 99%
“…Nitriles are employed widely as nitrogen nucleophilic reagents under acidic conditions in Ritter reactions,11 which means nitriles may have a better reactivity than N ‐unsubstituted amides in amidation reactions of simple arenes under acid conditions. Furthermore, our and others’ recent work12 also indicated that the use of nitriles as nitrogen nucleophiles instead of amides can make the synthesis of N ‐arylamides more accessible, because many amides are readily prepared from nitriles by hydrolysis.…”
Section: Methodsmentioning
confidence: 99%
“…In the past 20 years, remarkable progress has been made in the field of catalytic Ritter reaction in the presence of Brønsted or Lewis acids (e.g., SnCl 4 , BF 3 ·Et 2 O, AlCl 3 , etc.). 86 Reddy et al reported an efficient method for the preparation of α-aryl ethyl amides especially from vinyl arenes using an ethereal solution of tetrafluoroboric acid without any side reactions such as olefin polymerization (equation 123). 87 This method can also be applied to cyclohexene and cyclopentene to give 1-acetamidocylohexane and 1-acetamidocyclopentane, respectively, in good yields (equation 124 Ritter reaction has been applied in the total synthesis of natural products.…”
Section: Ritter Reactionmentioning
confidence: 99%
“…Other reactions in which a carbocation generated in situ is trapped by nitrile are referred to as Ritter-type reactions. 3 Thus, it was proposed to prepare new drug candidates through the Ritter reaction, by analogy to the work of Buc,4 condensing N-(hydroxymethyl)-saccharin with nitriles. (2), prepared in 92% yield from saccharin (1) and formaldehyde, 5 was reacted with equimolar amount of diverse nitriles in H 2 SO 4 at room temperature to afford, after work-up, the new crystalline amides (3) …”
Section: 2mentioning
confidence: 99%